Cost evaluation on performance of a PVD coated cutting tool during end-milling of Inconel 718 under MQL conditions - Saiful Bahri, Mohamed; Mohd Shahir, Kasim; Jaharah, A. Ghani (Taylor and Francis Ltd., 2016)
Interest is currently being focused on promoting environmentally friendly manufacturing without sacrificing productivity by utilising a minimum quantity lubrication (MQL) as a biodegradable coolant in the end-milling of Inconel 718. This study was carried out to compare the costs of applying machining and lubrication to the end-milling process at various cutting conditions. The high-speed cutting of Inconel 718 was performed using response surface methodology, and the optimisation conditions of the physical vapour deposition TiAlN/AlCrN-coated carbide tool consumption and the MQL were evaluated according to the performance of the tool, i.e. machining time and material removed. In addition, the number of cutting tool edges was taken into consideration when calculating the machining cost. The machining performance at maximum tool life, the minimum surface roughness and force were compared with the optimum conditions, and the results showed that the application of MQL and the use of a ball nose end mill under optimum conditions are competitive. The multi-objective optimisation of cutting parameters, with regard to the criteria for the maximum material removed (9.029 cm3) and the lowest total cost (US $ 0.11 cm−3), provided a combination of parameters that met the requirements for green manufacturing, i.e. by reducing the usage of cutting tools and the consumption of lubrication.